Pengaruh Religiusitas Terhadap Perilaku Distribusi Dan Perilaku Konsumsi Pedagang Muslim Di Kota Medan - Susilawati . (AGHNIYA : Jurnal Ekonomi Islam, 2020)
This research was motivated by a phenomenon that researchers still found in the field where there was still a deviation in the value of religiosity in the merchant's business behavior, for example lack of weighing of goods and incompatibility of sample items in the catalog provided for buyers with genuine goods for sale . This study aims to examine whether religiosity in the aspects of aqeedah, worship, sharia and morals affect the behavior of distribution traders and consumption behavior of Muslim traders in the city of Medan. This research is quantitative. Data collection uses a list of questions distributed to 100 Muslim traders whose business scale is classified as micro and domiciled / business location in the city of Medan. Data analysis uses the method of Multiple Linear Regression Analysis and Descriptive Analysis. The results showed simultaneously (F test), religiosity significantly affected the distribution behavior and consumption behavior of Muslim traders. Partially (t test), the religiosity of the moral aspects significantly influences the distribution behavior, while the religiosity of the aqeedah, worship and sharia aspects does not significantly influence the distribution behavior of Muslim traders.